2020
DOI: 10.1007/s10461-020-03112-9
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Interventions to Increase Point-of-Care HIV Testing and Linkage to Care Among Youth in the US: A Systematic Review

Abstract: HIV testing rates remain low among youth ages 13-24 in the US, with only 55% of HIV-positive youth aware of their serostatus. We conducted a systematic review to assess the utility of technology-based interventions to increase point-of-care youth HIV testing and linkage to care. We searched PubMed, Embase, CINAHL, and Cochrane CENTRAL for randomized controlled trials of technology-based interventions aimed at increasing point-of-care youth HIV testing, published between 2008 and 2020. All identified citations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Male youth who were unsure if they were transgender were also approximately twice as likely to have tested for HIV. These patterns might be a result of HIV prevention and treatment messaging that targets transgender individuals, or due to providers specifically encouraging HIV testing for transgender patients due to known vulnerability (Ibitoye et al, 2021; Sharma et al, 2019). These efforts could only succeed in settings in which gender-affirming messaging and care is available, so future research should explore regional and sociopolitical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Male youth who were unsure if they were transgender were also approximately twice as likely to have tested for HIV. These patterns might be a result of HIV prevention and treatment messaging that targets transgender individuals, or due to providers specifically encouraging HIV testing for transgender patients due to known vulnerability (Ibitoye et al, 2021; Sharma et al, 2019). These efforts could only succeed in settings in which gender-affirming messaging and care is available, so future research should explore regional and sociopolitical differences.…”
Section: Discussionmentioning
confidence: 99%
“…In less urbanized settings, the efforts to increase the HIV testing rates should focus on the trusted members of the local community, such as local health professionals, athletes, artists, academics or representatives of the religious communities, who may publicly discuss the issues surrounding HIV. The channels of communication with young people have evolved along with the technological advancement [29][30][31] . Previous studies indicated that interventions based on the use of new technologies can lead to an increase in HIV testing among young people 29 .…”
Section: Cues To Actionmentioning
confidence: 99%
“…The channels of communication with young people have evolved along with the technological advancement [29][30][31] . Previous studies indicated that interventions based on the use of new technologies can lead to an increase in HIV testing among young people 29 . In this way users are able to estimate individual risks by filling in a simple online test or understand the risks through video materials or computer games [29][30][31] .…”
Section: Cues To Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, because previous interventions did not enable contact with participants post-ED discharge, we could not collect follow-up data. Additionally, a recent systematic review shows very few technology-based interventions were developed to increase youth HIV testing in clinical settings and evaluated via randomized controlled trials; none of these included participants younger than 15 years [ 23 ].…”
Section: Introductionmentioning
confidence: 99%